FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PEMANEN PADA PT. CERENTI SUBUR KABUPATEN KUANTAN SINGINGI - Rizki Dwi Purwati; Nariman Hadi; Mashadi Mashadi (Fakultas Pertanian, Universitas Riau, 2018)
The purpose of this study was to determine how the economic productivity of labor andtechnical productivity of oil palm harvester at PT Cerenti Subur and to determine how muchinfluence social and economic factors of age, number of dependents, work experience,ethnicity, education level, and incentive / premium on labor productivity of oil palmharvester at PT. Cerenti Subur at Kuantan Singingi District. The analytical method used isthe method of Mathematical and multiple linear regression analysis. Results obtained showedthat the economic productivity of labor in the oil palm harvest of PT. Cerenti has an averageof IDR 146 133 per day and average technical productivity is of 2,474 Kg per day. Therelationship between labor productivity of harvester in PT. Cerenti has a significant effect onlabor productivity with a significant F test of 0.000 and has R square value of 0.919 whichmeans that relationship between productivity factor of age, number of dependents, workexperience, ethnicity, level of education and incentives is 91.9% while the rest 8.1% of laborproductivity of oil palm harvester at PT Cerenti were influenced by other factors which werenot included in the models studied.